Clitic and affix combinations : theoretical perspectives - Heggie, Lorie; Ordóñez, Fernando (J. Benjamins, 2005)
In this volume, the relationship between clitics and affixes and their combinatorial properties has led to a serious discussion of the interface between syntax, morphology, semantics, and phonology that draws on a variety of theoretical perspectives (e.g., HPSG, Optimality Theory, Minimalism). Clitic/affix phenomena provide a rich range of data, not only for the identification of an affix vs. clitic, but also for the best way to explain ordering constraints, some of which are contradictory. A range of languages are considered, including Romance and Slavic languages, as well as Turkish, Greek, Icelandic, Korean, and Passamaquoddy. Moreover, several articles consider dialectal microparameterization, notably in Spanish, French, and Occitan. This volume thus reflects current debate on issues such as clitic ordering constraints, the relationship of clitics to inalienable possession and the left periphery, and templatic approaches to affixes vs. clitics while examining a broad range of languages.
Keywords: Grammar, Comparative and general -- Clitics.; Grammar, Comparative and general -- Word formation.; Formation des mots.; Clitiques.; LANGUAGE ARTS & DISCIPLINES -- Grammar & Punctuation.; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Syntax.; Grammar, Comparative and general -- Clitics; Grammar, Comparative and general -- Word formation; Clitische elementen.; Affixen.; Electronic book.